The socio-economic consequences of the agribusiness model on the land reform beneficiaries in greater Tzaneen municipality, South Africa: The case of Elangeni Project - Rusenga, Clemence (Department of Sociology, 2017)
This study is situated in the field of land and agrarian reform. It explores the possible socioeconomic consequences of the large-scale commercial farming (LSCF) model on the land reform beneficiaries in Greater Tzaneen Municipality (GTM), South Africa. While the land reform programme seeks to reduce poverty, unemployment, and income inequality, among other things, the South African government has enforced the LSCF model in the land reform projects. The features of the model that the government is imposing on land reform beneficiaries are those of the agribusiness model. The agribusiness model is the current and dominant model of agrarian capitalism which increasingly organises agricultural production in the form of monoculture on an ever-increasing scale with the intense use of agricultural machinery and toxic chemicals along the growing use of genetically modified seeds (Stedile and Leon, 2014). Farm production, alongside upstream and downstream agricultural industries, is dominated by a decreasing number of large agribusinesses (Movement of Landless Rural Workers (MST), 2013:9-10). The concept, the agribusiness model, is used in the study to refer to the LSCF model. The study challenges the perspectives associating success or even the viability of land reform projects with the agribusiness model. It demonstrates a) the difficulties of the beneficiaries to follow the business model autonomously; b) the limitation of the state apparatus to support a costly agribusiness model; and c) the social distance of certain market-driven policies from the context and everyday lives of the beneficiaries and their families. The works of Ben Cousins, the MST and Archie Mafeje on the efficacy of the agribusiness model and the merits of the alternative small-scale model for the beneficiaries of agrarian reform influenced this study. Of the three, Archie Mafeje was more influential, and it is of academic interest that those writing on the LSCF model in the context of land reform in South Africa do not seem to take Mafeje's work more seriously especially that he is also against the LSCF model.